Platelet-Expressed TNFRSF13B (TACI) Predicts Breast Cancer Progression - Hinterleitner, Clemens; Zhou, Yanjun; Tandler, Claudia; Heitmann, Jonas S.; Kropp, Korbinian N.; Hinterleitner, Martina; Koch, André; Hartkopf, Andreas D.; Zender, Lars; Salih, Helmut R.; Maurer, Stefanie (Frontiers in Oncology, 2021)
Although treatment options in breast cancer have been improved significantly , predictive biomarkers for disease progression and metastasis are still lacking. Recent studies indicate that several TNF Receptor Superfamily members are involved in breast cancer cell proliferation and survival. Interestingly, TNFRSF13B (TACI) mRNA level were of prognostic relevance in breast cancer patients. In this study we provide evidence for TACI expression on platelets of breast cancer patients. The level of platelet-expressed TACI (pTACI) was significantly increased on platelets derived from breast cancer patients compared to healthy controls. Upon platelet activation, pTACI was downregulated on the platelet surface of healthy donors and breast cancer patients. Stimulation of TACI via BAFF or APRIL did not influence platelet activation and function. Remarkably, pTACI was particularly regulated during tumor progression in our breast cancer cohort. TACI expression levels on platelets were correlated with clinical parameters including tumor stage, occurrence of metastasis and tumor cell proliferation (Ki67). In conclusion, our data emphasize the potential use of platelets as a liquid biomarker in breast cancer.